Deciphering the fiber quality of Gossypium barbadense L. var. brasiliensis in La Convención, Cusco, Perú - Morales Aranibar, Luis (2024)
The quality of cotton fiber determines its value in the textile market, influencing agricultural profitability and the efficiency of textile processing. The selection of genotypes with superior fibers is a key factor for genetic improvement programs seeking adaptability and sustainability in the face of climate change. This demonstrates the strategic importance of this plant for sustainable agriculture and the global textile industry. The objective of this research was to decipher the fiber quality of Gossypium barbadense var. brasiliensis in the native Amazonian communities of La Convencion, Cusco-Peru, and to evaluate other critical aspects of native cotton that have not yet been identified. The methodology included non-probability sampling for accessibility, qualitative and quantitative analyses, and multivariate analyses. The fiber length (mm), micronaire index (maturity/fineness), fiber strength (gf/tex), length uniformity index (%), fiber elongation (%), maturation index (%), and short fiber index (%) were the fiber characteristics evaluated using the HVI method in cotton genotypes.